Taller de aprendizaje-servicio para integrar la responsabilidad social en la práctica preprofesional de estudiantes de Educación Inicial Facultad de Ciencias de la Educación y Humanidades Iquitos 2024 - Fababa Rodriguez, Maya (2025)
The study aimed to evaluate the effect of a service-learning workshop on integrating social responsibility into the pre-professional practice of early childhood education students at the Faculty of Education Sciences and Humanities, Iquitos, 2024. To this end, the methodological design considered a longitudinal, field-based, univariate evaluative approach. The sample consisted of 60 university students, who formed experimental and control groups with 30 participants, respectively. A standardized test was used as a data collection technique, and a written performance test was used as an instrument validated by experts. The research findings show that the implementation of the service-learning workshop had a positive and significant effect on the integration of social responsibility into the students' pre professional practice. In the control group, although there was an increase in post-test scores, the difference in core values was not considerable. In contrast, in the experimental group, a notable increase in post-test scores was recorded, reaching the excellent category on average. Statistical analysis confirmed this difference to be significant (p = .000 < .05), leading to the rejection of the null hypothesis. These results allow us to conclude that the workshop effectively contributed to the development of social responsibility in teacher training, strengthening the preparation of future teaching professionals.